CO2 capture and process reinforcement by hydrolysate of phosphogypsum decomposition products. Issue 36 (February 2020) - Zhang, Wei; Zhang, Fengzhen; Ma, Liping; Yang, Jing; Wei, Yi; Kong, Deqi
Graphical abstract: Highlights: A low energy consumption and effective technology for CCU was developed. Effects of the influencing factors on CO2 uptake. The kinetics of CO2 absorption has been studied. Abstract: In this work, we propose a novel, effective, energy efficient technology to reduce CO2 emissions and fully use the calcium in the solid waste by-product phosphogypsum (PG), by capturing CO2 from the PG decomposition product's hydrolysis solution. Experiments were conducted to investigate the technical feasibility and the influence of temperature and CO2 partial pressure on CO2 capture, as well as CO2 loading on CO2 sorption capacity. The results showed that > 90 % of the total calcium ions in the solution were converted into calcium carbonate (CaCO3 ). Furthermore, a decrease in temperature and an increase in CO2 partial pressure improved CO2 uptake, with the latter having a greater effect on CO2 capture capacity than the former. Moreover, kinetic analysis demonstrated that a higher temperature and CO2 partial pressure increased the absorption rate; and showed that the CO2 absorption rate is highly affected by the CO2 loading levels. The thermodynamic analysis indicated that CO2 absorption heat significantly declined as a function of increasing CO2 loading. CaO from the calcination of carbonate was added to the hydrolysis solution and significantly enhanced its CO2 capture ability. Thus, the hydrolyate of PG decomposition products in combination with CaO reinforcement may be a promising method for CO2 capture.